IMPLEMENTASI STRATEGI DIGITAL MARKETING MELALUI TIKTOK UNTUK MENINGKATKAN OMSET PENJUALAN DALAM PERSPEKTIF PEMASARAN SYARIAH: STUDI KASUS PADA TOKO KOSMETIK IFA BEAUTY GLOBAL KRAKSAAN - Himmah, Mufidatul; Kurnia Setiawan, Eva (Penerbit Lafadz Jaya, 2025)
The rapid development of internet technology has significantly transformed business marketing strategies. Digital marketing has become an effective alternative for reaching a broad and fast consumer base through digital platforms. TikTok, as a popular social media platform, offers opportunities for product promotion and increased online sales. This study analyzes the implementation of digital marketing strategies via TikTok to enhance sales turnover at Ifa Beauty Global Kraksaan Cosmetics Store and evaluates its compliance with Islamic marketing principles. The research employs a qualitative descriptive method with a case study approach, including direct observation, in-depth interviews, and documentation of marketing activities. The findings indicate that digital marketing strategies on TikTok—such as creating educational content, live streaming, and utilizing TikTok Shop features—positively impact sales turnover. Moreover, the marketing practices align with Islamic values, including honesty (shiddiq), transparency (tabligh), responsibility (amanah), and fair, humane treatment of consumers (humanistic). This study suggests that strategic use of TikTok social media can improve sales performance while adhering to ethical standards of Islamic marketing in the digital era.